Prevalence of Under Nutrition and its Effects on Response to Malaria Treatment Among Children Under Five Years at Ahero and Homabay Hospitals, Western Kenya - Kagombe, Elizabeth Achieng (JOOUST, 2017)
Nutritional status of a person with malaria infection is thought to contribute to host treatment outcome. However, limited studies have investigated the association despite the widespread concern with nutrition in malaria endemic areas. The objective of the study was to determine the prevalence of under nutrition and its effects on response to malaria treatment among children under five years in Ahero Sub County and Homabay County Hospitals in Western Kenya. Specific objectives were to determine the prevalence of under nutrition, (underweight and stunting) in children below five years with uncomplicated malaria in Ahero sub county hospital and Homabay County hospital, to compare the impact of Artemether Lumefantrine against Clindamycin plus Quinine in the treatment of uncomplicated malaria in children below five years and to evaluate the impact of under nutrition on the treatment outcome by Artemether Lumefantrine and Clindamycin plus Quinine. The study design was an open -label, randomized clinical trial in a random sample of 384 children aged below five years diagnosed with uncomplicated Plasmodium falciparum malaria in Ahero sub County Hospital and Homabay County Hospital. Anthropometric measurements were carried out to determine the nutritional status of the children; In addition, the eligible participants were randomized to receive Clindamycin plus quinine or Artemether-lumefantrine (AL) for treatment of uncomplicated malaria. The children were followed up for 28 days to monitor body weight and height, clinical and parasitological parameters of treatment response. Outcomes included parasite clearance at days 2 and 3 and risk of recurrent parasitemia after 28 days of follow-up. Data entry, cleaning and analysis was done using the statistical package for Social Sciences (SPSS version 10.0) and indices of nutritional status were computed using the EPI-Info (version 6.0) packages. The results of the study established that prevalence of malnutrition in the study was as follows; underweight was 6 % (n=23) stunting was 12% (n=45). The body weight increased over the 28 day follow up period. The initial mean weight was 13.03kg while the mean weight on day 28 was 13. 7kg. The proportion of children with stunting was comparable between the female and male children: 40% verse 60%, p=0.06. Generally, the prevalence of underweight was comparable between the treatment arms (p=0.08). Similarly, the prevalence of stunting was not significantly different between the treatment arms (p=0.34). Of the 384 children enrolled in the study, cure rate was high in the Artemether group (96.5%) compared to the Clindamycin group (44.2%). Children who were underweight were 0.69 times less likely to be cured compared to those who were not underweight, but this difference was not significantly different from that of children who had no underweight (p = 0.429). Treatment outcomes were known for 43 of the 45 (95 .6%) children with stunting. Overall, stunted children were 1.15 times more likely to be cured compared with children who were not stunted, but this difference was not statistically significant (p=0.704). In conclusion, no association between under nutrition (underweight and stunting) and treatment outcome was observed. Future research to investigate on pharmacokinetics on drug metabolism comparing malnourished children against normal children will be useful. In addition, further research is suggested on the impact of under nutrition on response to malaria treatment using Artemether Lumefantrine alone on children less than five years. The findings of this study will be useful to the Ministry of health and other policy makers in formulating guidelines to improve management of children with malaria taking into consideration their nutritional status, and to integrate nutrition in malaria programmes.